Tata Kelola Keuangan Sederhana bagi UMKM di Kapuk Muara - Wiwit Irawati; Lioni Indrayani; Harry Barli (LPPM UNIVERSITAS DIAN NUSWANTORO, 2020)
Based on the Regulation Number 20 Year 2020 regarding Small Micro Medium Enterprise, Dian Mandiri Foundation is committed to be an asset for Indonesia in accordance with its vision which is to transform life through development of Small Micro Medium Enterprise. The commitment to develop enterprise is attained by helping business development their partners. In managing development of business, the partners often face problem in bookkeeping their business, especially at this pandemic covid-19. Therefore, by doing the community service activity from Universitas Pamulang, it is expected to become the solution to finance governance problem of Dian Mandiri cooperative's partners.